Validation of the Finnish Person-Centered care Climate Questionnaire-Patient and testing the relationship with individualized care - Stolt Minna; Koskenvuori Janika; Edvardsson David; Katajisto Jouko; Suhonen Riitta (Wiley, 2025)
Aims
The aim of the study was two-fold: (1) to test the psychometric properties of the Person-Centered care Climate Questionnaire-Patient-Finnish version (PCQ-P-Fin), and (2) to examine the associations between older patients’ perceptions of the PCC climate and their perceptions of individuality in care delivered within acute care settings for older people.
Design
An exploratory, correlational, cross-sectional survey design.
Methods
The study was conducted within acute care settings for older people with heart failure (n = 111, response rate 54%). Data were collected with self-completed questionnaires, the Person-Centered care Climate Questionnaire-Patient version (PCQ-P-Fin) and the Individualized Care Scale-Patient (ICS-Patient-B), between 6/2016 and 5/2017. Data were analysed using descriptive statistics, Pearson's correlation coefficients, exploratory factor analysis and a Rasch analysis.
Results
The PCQ-P-Fin showed satisfactory structural, construct and concurrent validity and high reliability. The ICS-B-Patient and the PCQ-P-Fin correlated strongly positive suggesting an association between the perceptions of individuality in care and the care climate.
Conclusion
The PCQ-P-Fin is a useful, reliable and valid tool. Characteristics of the care environment, especially the climate and the extent to which this is perceived to be person-centred, may be used to enhance perceptions of individualised care.